Gintonin, a ginseng-derived exogenous lysophosphatidic acid receptor ligand, enhances blood-brain barrier permeability and brain delivery - Kim, Do-Geun; Jang, Minhee; Choi, Sun-Hye; Kim, Hyeon-Joong; Jhun, Hyunjhung; Kim, Hyoung-Chun; Rhim, Hyewhon; Cho, Ik-Hyun; Nah, Seung-Yeol (Elsevier BV, 2018)
Gintonin is a ginseng-derived G-protein-coupled lysophosphatidic add (LPA) receptor ligand. Gintonin induces [Ca2+]; transient and biological effects through LPA receptor and increases the permeability of the blood-brain barrier (BBB). However, little is known about its mechanisms on the BBB. We examined the in vitro effects of gintonin using primary human brain microvascular endothelial cells (HBMECs) and the in vivo effects of gintonin on brain delivery. Fluorescent-labeled gintonin bound to HBMECs and co-localized with the LPA1 receptor. Gintonin caused morphological changes, increased junctional spaces, and induced differential effects on junctional protein levels such as vascular endothelial-cadherin, occludin, zonula occludens 1, and claudin-5, in HBMECs. Gintonin led to the opening of gap junctions between HBMECs, and allowed Texas red-dextran to enter the cells, which was blocked by Ki16425, an LPA1/3 receptor antagonist, and Y27632, a Rho-associated kinase inhibitor. Intravenous administration of gintonin in rodents also increased the delivery of fluorescein isothiocyanate-dextran or erythropoietin to the brain. Furthermore, fluorescent-labeled gintonin bound to endothelial cells, neurons, and glia in the brain following its entry. Our findings show that gintonin facilitates entry to the brain through the paracellular pathway. Thus, gintonin may bean herbal medicine-derived candidate to overcome the BBB in drug delivery. (C) 2018 Elsevier B.V. All rights reserved.